Managing quality customer service : a practical guide for establishing a service operation - Martin, William B. (Fifty-Minute series., 1989)
Annotation This practical, self-study book has been developed to help you establish and manage a quality service operation. Learn how to determine customer needs, how to effectively and efficiently meet those needs, and how to continually measure your service level.